How do you solve -4(2x-1) = -6(x+2) -2?
1 Answer
May 22, 2016
Explanation:
Given,
-4(2x-1)=-6(x+2)-2
Expand the brackets.
-8x+4=-6x-12-2
Simplify.
-8x+4=-6x-14
Subtract
-8x+4color(white)(i)color(red)(-4)=-6x-14color(white)(i)color(red)(-4)
-8x=-6x-18
Add
-8xcolor(white)(i)color(red)(+6x)=-6xcolor(white)(i)color(red)(+6x)-18
-2x=-18
Divide both sides by
color(red)((color(black)(-2x))/(-2))=color(red)((color(black)(-18))/(-2))
color(green)(|bar(ul(color(white)(a/a)color(black)(x=9)color(white)(a/a)|)))